DRAGONES, CREATIVIDAD Y GENERACIÓN DE CONOCIMIENTO Una consideración modular sobre la Investigación en la Facultad de Derecho - David Valencia Villamizar (Via Inveniendi Et Iudicandi, 2013)
This article shows, from an alternative optic to understanding the Law, a proposal, wich analyzes the fundamental issues of legal research, especially in the Faculty of Law of the Santo Tomás University, that is characterized by his modular system.